2013
DOI: 10.3390/min3040367
|View full text |Cite
|
Sign up to set email alerts
|

Geobiological Cycling of Gold: From Fundamental Process Understanding to Exploration Solutions

Abstract: Microbial communities mediating gold cycling occur on gold grains from (sub)-tropical, (semi)-arid, temperate and subarctic environments. The majority of identified species comprising these biofilms are β-Proteobacteria. Some bacteria, e.g., Cupriavidus metallidurans, Delftia acidovorans and Salmonella typhimurium, have developed biochemical responses to deal with highly toxic gold complexes. These include gold specific sensing and efflux, co-utilization of resistance mechanisms for other metals, and excretion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(32 citation statements)
references
References 89 publications
2
30
0
Order By: Relevance
“…This was higher than the 50% of platinum retained in the blank control, suggesting the ability of E. coli to facilitate platinum solubilization, transport, and precipitation, thus affecting the dispersion and re-concentration of Pt in surface environments. Microbes can also influence redox and pH conditions and are involved in the formation and secretion of ligands in soils and surface-and groundwaters [8][9][10]41]. In this experiment, the pH of the column outlet solution varied from 5.5 to 6.6 (average of 6.5) throughout the experiment, and the pH in the control column did not significantly change.…”
Section: Discussionmentioning
confidence: 99%
“…This was higher than the 50% of platinum retained in the blank control, suggesting the ability of E. coli to facilitate platinum solubilization, transport, and precipitation, thus affecting the dispersion and re-concentration of Pt in surface environments. Microbes can also influence redox and pH conditions and are involved in the formation and secretion of ligands in soils and surface-and groundwaters [8][9][10]41]. In this experiment, the pH of the column outlet solution varied from 5.5 to 6.6 (average of 6.5) throughout the experiment, and the pH in the control column did not significantly change.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the possibility of supergene Au enrichment linked to biogenic-related processes has been a topic of discussion Southam et al, 2009;Fairbrother et al, 2012;Shuster and Southam, 2015). In this way, very fine (1-25-µm) reniform Au particles have been reported related to biological activity (Lengke et al, 2006a;Reith et al, 2009Reith et al, , 2013Southam et al, 2009). Moreover, other morphologies, including fine octahedral and hexagonal crystals (5-15 µm) have been attributed to similar biological genesis (Lengke et al, 2006b, c;Southam et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, sulfate-reducing bacteria are able to reduce thiosulfate complexes to hydrogen sulfide (H2S), leading to metal ion precipitation and subsequent formation of metal sulfides via bacterial detoxification. These processes destabilize the Au in solution, which can be incorporated into the newly formed sulfide as nanoparticles and or/ bioforms (Lengke and Southam, 2006a;2007;Reith et al, 2007;Reith et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Where metal mobilization, transfer and immobilization are important for spatial distribution of metals, the role of microbes in Au and some pathfinder elements serves as examples. Several workers (e.g., Savvaidis et al, 1998;Reith, 2003;Reith et al, 2007;Southam et al, 2009;Reith et al, 2013) provide good reviews for gold-microbe interactions. In vitro studies on Au microbial interactions have demonstrated the capacity of a common soil bacterium, Bacillus subtilis, to take up mobile dissolved Au 3+ ions and transform them into colloidal gold particles.…”
Section: Immobilization and Biomineralization Of Metalsmentioning
confidence: 98%